Biliar reflux by incompetence of the sphincter of oddi post endoscopic retrograde cholangiopancreatography, as cause of cholangiolar abscesses and cardiac vegetations - Sánchez-Reyes, Karina; Alcántara-Huerta, Beatriz; Aguilera-Hernández, Estrella; Cerrillo-Ávila, Javier; Baez-Perez, Estela; Rodríguez-Negrete, Elda V. (International Journal of Research in Medical Sciences, 2023)
The term sphincter of Oddi dysfunction (SOD) encompasses a heterogeneous group of patients with a clinical syndrome characterized by abdominal pain (biliary colic or pancreatic pain), attributed to motor alterations of the SO that cause obstruction of the flow of bile and pancreatic juice (intermittent or fixed acalculous obstruction) or reflux of the same through the sphincter. Its diagnosis and treatment are controversial. We presented the case of a patient with sphincter of Oddi incompetence as a rare cause of jaundice, abdominal pain and cholangiolar abscesses due to sphincter incompetence from multiple endoscopic procedures and a history of cholecystectomy. We review the epidemiology, etiology, diagnostic criteria and management, both conservative and surgical.